2013
DOI: 10.2169/internalmedicine.52.8498
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pirfenidone in Patients with Advanced-stage Idiopathic Pulmonary Fibrosis

Abstract: Objective To assess the efficacy of pirfenidone in patients with advanced-stage idiopathic pulmonary fibrosis (IPF), we conducted a retrospective study of patients who received pirfenidone therapy. In addition, the combined effects of inhaled N-acetylcysteine (NAC) and pirfenidone were evaluated. Methods Eligible patients had a clinical and radiologic diagnosis of advanced-stage IPF (stages of severity III&IV). Patients who exhibited a relative decline in forced vital capacity (FVC) of 10% or more within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…In an open-label phase 2 study ( n = 54), Raghu et al[10] demonstrated that pirfenidone could stabilize or improve lung function (in 70.7% of patients at 6 months) in IPF patients, some of whom were at an advanced stage (FVC range, 26–108% predicted; DLco range, 8–104% predicted). A retrospective study of advanced IPF ( n = 18, stage III and IV according to JRS criteria) also showed that pirfenidone stabilized FVC decline in 44% of patients over 6 months and that the median change in their FVC was +120 mL [12]. Postmarketing surveillance of 1,371 IPF patients, some of whom were at an advanced stage (stage III and IV in 67.4% of patients), showed that pirfenidone stabilized both the vital capacity and subjective symptoms in most patients (70–80%) treated for ≥6 months [13].…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label phase 2 study ( n = 54), Raghu et al[10] demonstrated that pirfenidone could stabilize or improve lung function (in 70.7% of patients at 6 months) in IPF patients, some of whom were at an advanced stage (FVC range, 26–108% predicted; DLco range, 8–104% predicted). A retrospective study of advanced IPF ( n = 18, stage III and IV according to JRS criteria) also showed that pirfenidone stabilized FVC decline in 44% of patients over 6 months and that the median change in their FVC was +120 mL [12]. Postmarketing surveillance of 1,371 IPF patients, some of whom were at an advanced stage (stage III and IV in 67.4% of patients), showed that pirfenidone stabilized both the vital capacity and subjective symptoms in most patients (70–80%) treated for ≥6 months [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on some of these studies the first IPF-specific drug, pirfenidone, has recently been licenced for use in Europe [95]. In the past year, safety reports of pirfenidone in real-life practice have been published both from Japan and Europe, confirming that pirfenidone is well tolerated and can improve progression-free survival in IPF [96][97][98]. However, this is just the first step on a long road towards successful treatment of IPF, and we should keep walking with it clear in our mind that combinations of various agents may be more effective [99].…”
Section: Advances In Understanding the Pathogenetic Mechanisms Of Ipfmentioning
confidence: 99%
“…1). Eight studies were conducted in Japan (Bando et al, 2010[3]; Homma et al, 2012[14]; Huang et al, 2015[15]; Kamio et al, 2014[17]; Okuda et al, 2016[22]; Sakamoto et al, 2013[30], 2015[31]; Tomioka et al, 2005[36]), three in multi-countries (Behr et al, 2009[6], 2016[5]; Raghu et al, 2012[24]) and one in United States (Martinez et al, 2014[20]). Only two types of antioxidants (N-Acetylcysteine (NAC) (Bando et al, 2010[3]; Behr et al, 2009[6], 2016[5]; Homma et al, 2012[14]; Huang et al, 2015[15]; Martinez et al, 2014[20]; Okuda et al, 2016[22]; Raghu et al, 2012[24]; Sakamoto et al, 2013[30], 2015[31]; Tomioka et al, 2005[36]) and lecithinized superoxide dismutase (PC-SOD) (Kamio et al, 2014[17]) were reported in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Various clinical studies have reported the efficacy of antioxidant treatment (such as N-acetylcysteine (NAC) and lecithinized superoxide dismutase (PC-SOD)) for IPF (Bando et al, 2010[3]; Behr et al, 2009[6], 2016[5]; Homma et al, 2012[14]; Huang et al, 2015[15]; Kamio et al, 2014[17]; Martinez et al, 2014[20]; Okuda et al, 2016[22]; Raghu et al, 2012[24]; Sakamoto et al, 2013[30], 2015[31]; Tomioka et al, 2005[36]). Several studies found that NAC treatment had a beneficial effect on lung function in IPF patients and significantly delayed disease progression (Behr et al, 2009[6]; Homma et al, 2012[14]; Huang et al, 2015[15]; Okuda et al, 2016[22]; Sakamoto et al, 2013[30], 2015[31]) whereas few studies reported that NAC treatment had no benefit and did not significantly improve the lung function of patients with IPF (Bando et al, 2010[3]; Behr et al, 2016[5]; Martinez et al, 2014[20]; Raghu et al, 2012[24]). A study by Tomioka et al (Tomioka et al, 2005[36]) showed that N-acetylcysteine aerosol treatment might delay disease progression, but did not improve pulmonary function or quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation